Knitting hypercrosslinked conjugated microporous polymers with external crosslinker. (23rd July 2015) - Tan, Liangxiao; Li, Buyi; Yang, Xinjia; Wang, Weixing; Tan, Bien
Abstract: A new series of hypercrosslinked polymers were efficiently synthesized by knitting rigid aromatic building blocks using a novel external crosslinker (1, 4-dimethoxybenzene, DMB) which result in a conjugated microporous structure. This knitting hypercrosslinked conjugated microporous polymers (HCCMPs) are predominantly microporous and exhibit high surface area of up to 800 m 2  g −1, which also show comparable gas uptake properties reaching 1.14 wt. % H2 adsorption at 1.13 bar/77 K, and 12.72 wt. % CO2 adsorption at 1.13 bar/273 K, respectively. The extended π-conjugated structure and the three-dimensional network of π–π stacked aryl rings enable these HCCMPs good luminescence properties and high electrical conductivity. Graphical abstract: Highlights: Knitting rigid aromatic building blocks using a novel external crosslinker. The knitting hypercrosslinked conjugated microporous polymers (HCCMPs). HCCMPs have good luminescence properties and high electrical conductivity.